Potential dual expansion of domesticated donkeys revealed by worldwide analysis on mitochondrial sequences (2020)
Molecular studies on donkey mitochondrial sequences have clearly defined two distinct maternal lineages involved in domestication. However, domestication histories of these two lineages remain enigmatic. We therefore compared several population characteristics between these two lineages based on global sampling, which included 171 sequences obtained in this study (including Middle Asian, East Asian, and African samples) plus 536 published sequences (including European, Asian, and African samples). The two lineages were clearly separated from each other based on whole mitochondrial genomes and partial non-coding displacement loop (D-loop) sequences, respectively. The Clade I lineage experienced an increase in population size more than 8 000 years ago and shows a complex haplotype network. In contrast, the population size of the Clade II lineage has remained relatively constant, with a simpler haplotype network. Although the distribution of the two lineages was almost equal across the Eurasian mainland, they still presented discernible but complex geographic bias in most parts of Africa, which are known as their domestication sites. Donkeys from sub-Saharan Africa tended to descend from the Clade I lineage, whereas the Clade II lineage was dominant along the East and North coasts of Africa. Furthermore, the migration routes inferred from diversity decay suggested different expansion across China between the two lineages. Altogether, these differences indicated non-simultaneous domestication of the two lineages, which was possibly influenced by the response of pastoralists to the desertification of the Sahara and by the social expansion and trade of ancient humans in Northeast Africa, respectively.